EFEKTIVITAS MEDIA GRAFIS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN BAGI ANAK BERKESULITAN BELAJAR KELAS II DI SDN 17 JAWA GADUT - Defi Fitria Sari (Universitas Negeri Padang, 2014)
Abstrak Background problem in this study is the low reading ability of children in the beginning. Researchers provide intervention using graphic media. The purpose of this study is to prove the effectiveness of graphic media can improve a child's ability to read the beginning of the X-type learning disabilities research is quantitative with the experimental method in the form of Single Subject Design (SSD), the multiple baseline design cross variables. Based on the results of research conducted, it can be concluded graphic media effectively to improve reading skills learning disabilities for children beginning to read X class II in SDN 17 Gadut Java. The results of this study if it can be taken into consideration for teachers to use graphic media in learning Indonesian, especially in beginning reading. Kata kunci: Anak berkesulitan belajar; Kemampuan membaca permulaan; Media grafis.